(untitled) ([Great Britain], 2005)
Nano-CMOS Circuit and Physical Design integrates the nanometer process, device manufacturability, advanced circuit design, and related physical implementation into a single, seamless approach to advanced semiconductor technology. This comprehensive volume explores new developments in devices and processing; presents design issues, paying special attention to technology/design interactions such as signal integrity and interconnects; and addresses the impact of design for manufacturability and variability. Important topics include: Nano-CMOS process scaling issues and implications on design; subwavelength optical lithography; physics and theory of operation issues and solutions and design for manufacturability and variability
Keywords: Metal oxide semiconductors, Complementary,Integrated circuits,Mạch tích hợp,Chất bán dẫn ôxit kim loại, bổ sung; Design and construction,Design and construction,Thiết kế và xây dựng,Thiết kế và xây dựng